Emergence of a cholecystokinin/sulfakinin signalling system in Lophotrochozoa. Issue 1 (December 2018) - Schwartz, Julie; Dubos, Marie-Pierre; Pasquier, Jérémy; Zatylny-Gaudin, Céline; Favrel, Pascal
Abstract Chordate gastrin/cholecystokinin (G/CCK) and ecdysozoan sulfakinin (SK) signalling systems represent divergent evolutionary scenarios of a common ancestral signalling system. The present article investigates for the first time the evolution of the CCK/SK signalling system in a member of the Lophotrochozoa, the second clade of protostome animals. We identified two G protein-coupled receptors (GPCR) in the oysterCrassostrea gigas (Mollusca), phylogenetically related to chordate CCK receptors (CCKR) and to ecdysozoan sulfakinin receptors (SKR). These receptors, Cragi-CCKR1 and Cragi-CCKR2, were characterised functionally using a cell-based assay. We identified di- and mono-sulphated forms of oyster Cragi-CCK1 (pEGAWDY(SO3 H)DY(SO3 H)GLGGGRF-NH2 ) as the potent endogenous agonists for these receptors. The Cragi-CCK genes were expressed in the visceral ganglia of the nervous system. The Cragi-CCKR1 gene was expressed in a variety of tissues, while Cragi-CCKR2 gene expression was more restricted to nervous tissues. Anin vitro bioassay revealed that different forms of Cragi-CCK1 decreased the frequency of the spontaneous contractions of oyster hindgut. Expression analyses in oysters with contrasted nutritional statuses or in the course of their reproductive cycle highlighted the plausible role of Cragi-CCK signalling in the regulation of feeding and its possible involvement in the coordination of nutrition and energy storage in the gonad. This study confirms the early origin of the CCK/SK signalling system from the common bilaterian ancestor and delivers new insights into its structural and functional evolution in the lophotrochozoan lineage.